PHYTOCHEMISTRY, PHARMACOLOGY AND MEDICINAL PROPERTIES OF CORIANDRUM SATIVUM L (Academicia Globe: Inderscience Research, 2022)
This article is devoted to open medicinal properities of Coriandrum sativum L and its usage in pharmacology.